Genetic affinities among the lower castes and tribal groups of India: inference from Y chromosome and mitochondrial DNA - Reddy B Mohan (BMC Genetics, 2006)
Abstract Background India is a country with enormous social and cultural diversity due to its positioning on the crossroads of many historic and pre-historic human migrations. The hierarchical caste system in the Hindu society dominates the social structure of the Indian populations. The origin of the caste system in India is a matter of debate with many linguists and anthropologists suggesting that it began with the arrival of Indo-European speakers from Central Asia about 3500 years ago. Previous genetic studies based on Indian populations failed to achieve a consensus in this regard. We analysed the Y-chromosome and mitochondrial DNA of three tribal populations of southern India, compared the results with available data from the Indian subcontinent and tried to reconstruct the evolutionary history of Indian caste and tribal populations. Results No significant difference was observed in the mitochondrial DNA between Indian tribal and caste populations, except for the presence of a higher frequency of west Eurasian-specific haplogroups in the higher castes, mostly in the north western part of India. On the other hand, the study of the Indian Y lineages revealed distinct distribution patterns among caste and tribal populations. The paternal lineages of Indian lower castes showed significantly closer affinity to the tribal populations than to the upper castes. The frequencies of deep-rooted Y haplogroups such as M89, M52, and M95 were higher in the lower castes and tribes, compared to the upper castes. Conclusion The present study suggests that the vast majority (>98%) of the Indian maternal gene pool, consisting of Indio-European and Dravidian speakers, is genetically more or less uniform. Invasions after the late Pleistocene settlement might have been mostly male-mediated. However, Y-SNP data provides compelling genetic evidence for a tribal origin of the lower caste populations in the subcontinent. Lower caste groups might have originated with the hierarchical divisions that arose within the tribal groups with the spread of Neolithic agriculturalists, much earlier than the arrival of Aryan speakers. The Indo-Europeans established themselves as upper castes among this already developed caste-like class structure within the tribes.